Understanding the relationship between BMI and sexual dysfunction: can DSM-5 shed light into this topic? - Roxo, L.; Virgolino, A.; Costa, J.; Alarcão, V. (Revista Internacional de Andrología, 2019)
Introduction: The links between body weight and sexuality, notably sexual dysfunction (SD), are intricate and not yet fully understood. A more individual-focused evaluation of sexual difficulties, as recently provided by the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), contributes to improve precision in SD diagnosis and has the potential to advance our knowledge on the association between body weight and SD. Objectives: To identify gender differences in sexual behaviors and SD among Portuguese men and women within different classes of body mass index (BMI); and to explore the association between BMI and SD by using the new DSM-5 criteria. Material and methods: Face-to-face interviews followed by self-completed questionnaires of primary healthcare users in Portugal (n = 323). Data on sociodemographic variables, BMI, sexual behaviors and SD were collected. DSM-5 criteria were used to assess sexual dysfunction. The International Index of Erectile Function (IIEF) and the Female Sexual Function Index (FSFI) for men and women, respectively, were used for comparison purposes. Results: Overweight and obese women reported less sexual partners, less satisfaction with sexual frequency and rated sexual life as less important. These differences were not found among men. Normal weight men and women had a higher score of IIEF and FSFI, respectively, than those overweight and obese. No significant effects of BMI scale on SD following DMS-5 were detected. Conclusions: Women's sexual function is more impacted by BMI than men's. Individual-orientated approaches, as proposed in DSM-5, may allow a better understanding on the relation between body size and sexuality in both genders.